2008
DOI: 10.1007/s10344-008-0178-7
|View full text |Cite
|
Sign up to set email alerts
|

Leptospira antibodies in wild boars (Sus scrofa) in Slovenia

Abstract: Serum samples collected from 437 shot wild boars (Sus scrofa) were tested for the presence of antibodies against Leptospira interrogans sensu lato in wild boar in Slovenia. Assessment of leptospira-specific antibodies was performed by microscopic agglutination test. Antibodies against at least one of the pathogenic serovars were detected in 200 (45.8%) sera. From 200 positive samples, 100 samples (50%) had positive titre against a single serovar, while 100 (50%) samples had positive titres against two or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 13 publications
5
27
1
Order By: Relevance
“…Nevertheless, significant statistical differences (P > 0·05) were not found ( Table 2). These findings corroborate the data presented in studies from Slovenia [6], Germany [14] and the Czech Republic [9].…”
supporting
confidence: 94%
See 2 more Smart Citations
“…Nevertheless, significant statistical differences (P > 0·05) were not found ( Table 2). These findings corroborate the data presented in studies from Slovenia [6], Germany [14] and the Czech Republic [9].…”
supporting
confidence: 94%
“…This finding is consistent with other serosurvey studies in which low titres were frequently observed [6,9,10]. This fact is the reason why, for further statistical analysis, the authors considered sera samples with titres 51:50 as positive, bearing in mind that in epidemiological studies it is much more important to establish the animals' exposure to the aetiological agent independently of determining if there is any evidence of current infection [8,11].…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Feral swine social groups, called sounders, are comprised of sows and their offspring. This distinction between sexes (Table 1) was not replicated in other studies [25,26], but may have been merely a function of sample size since we sampled at least five times the number of animals as these other studies. As a result, males occupy larger home ranges than females [24].…”
Section: Discussionmentioning
confidence: 79%
“…Although serological prevalence of leptospirosis in feral swine has been examined in the United States and other countries [11,[13][14][15][16][17], we are unaware of any national scale efforts in the United States to quantify leptospiral shedding in the species. Since pathogenic leptospires have a predilection for the kidneys of infected swine [4], we tested kidneys and paired serum of feral swine collected in counties previously identified as antibody positive [11].…”
Section: Introductionmentioning
confidence: 99%